Developing an induction and mentoring programme to assist newly appointed principals in selected education districts in the Free State province - Thobi, Lepono Desmond (Welkom : Central University of Technology, Free State, 2010)
Newly appointed principals are facing enormous challenges as managers of their schools today. When they are first appointed, many begin their work with a lot of uncertainty, anxiety and frustration due to lack of assistance, guidance and support. As principals of schools, newly appointed principals are expected to perform to the best of their ability in order to ensure that their schools succeed and achieve the best possible results. The constant changes in education require the newly appointed principal to adapt to these changes and to acquire the necessary knowledge and skills in order to implement the policies, regulations and procedures. Without proper guidance and support most newly appointed principals are unlikely to succeed. It is therefore necessary that these principals are exposed to induction and mentoring opportunities in order to capacitate them and enhance their performance and their competencies. Newly appointed principals should first be exposed to an induction programme after their arrival at work. The induction programme should subsequently be followed by a mentoring programme whereby a mentor is assigned to the newly appointed principal. The purpose of this study is to develop an induction and mentoring programme to assist newly appointed principals in selected education districts in the Free State province. The qualitative approach is used in this study as it seeks to represent reality from the perspectives of the participant, without interfering with or biasing that perspective, in their own words and using their own concepts. To analyse data for this study the researcher used coding in order to categorise data into themes. The findings of this study reveal that all the schools do not have a policy for the induction and mentoring of newly appointed principals. The study also revealed that schools did not have a formal induction and mentoring programme and as a result, there were not enough induction and mentoring opportunities for new principals in their first year as principals. It was also found that no monitoring and evaluation was done due to lack of formal programmes in the schools. It is recommended that a policy for the induction and mentoring programme be formulated in schools. Those responsible for inducting and mentoring newly appointed principals must ensure that the programme is properly managed in order for it to succeed. The induction and mentoring programme should be thoroughly planned in order to meet the needs of the newly appointed principals. Before implementing any programme it is essential that the training needs of newly appointed principals are identified. These needs should then be prioritised in relation to the needs they are intended to serve. The induction programme should have carefully formulated objectives so that the programme can address the needs of newly appointed principals appropriately. It is important therefore that this programme be monitored at all times in order to ascertain whether it is meeting the objectives of the programme. The induction and mentoring programme for newly appointed principals should be evaluated at the end in order to determine the success and impact of the programme on newly appointed principals.
Thesis (Ph.D.) - Central University of Technology, Free State, 2010
Keywords: Central University of Technology, Free State - Dissertations; School principals - South Africa - Free State; Educational leadership; School principals - In-service training; Mentoring in education; Dissertations, academic - South Africa - Welkom